COMPARISON OF NOUNS REDUPLICATION IN INDONESIAN AND JAPANESE LANGUAGE - Stephanus Mangga (University of Kuningan, 2018)
This article is a qualitative description of the nouns reduplication comparison in Indonesian and Japanese language. Nouns are restricted to the category on the noun which can be counted (KBK). The data were taken from library source and analyzed by comparing the elements of similarity and difference. As result, it was found that there are similarities and differences between KBK’s reduplication of Indonesian and Japanese language. The equations include three items, namely; a) it has simple type without affixes, b) it has complex type with changes of consonants, and c) it functions to declare the indefinite category of the group. While the differences consist of four items and they are not found in Japanese language. Those four items are: a) it is in the form of simply affix, b) it is in the complex form with the repetition of consonants, c) it functions to show group category indefinite, and d) it functions as types of category indefinite. Those differences prove that reduplication of KBK in Indonesian language are more productive that reduplication of KBK in Japanese language.Keywords: reduplication, noun, Indonesian language, Japanese language